Penerapan Metode Double Exponential Smoothing dan Moving Average pada Peramalan Persediaan Spare Part Oil Filter di PT. X Cabang Karawang - Sigit, Radyta Alicia Pramestia; Herwanto, Dene (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
One of the most important elements in a trading company is inventory. Inventories are merchandise purchased and then stored for further resale in operations. The purpose of this research is that PT. X Karawang Branch can determine the right amount of inventory for oil filter spare parts so that their availability is maintained and can meet consumer needs. Double Exponential Smoothing and Moving Average are methods that are in accordance with the problems that occur at PT. X Karawang Branch, especially in the problem section of determining supply of oil filter spare parts. Forecasting oil filter product inventory using the double exponential smoothing method gives a result of 874 with an MSE value of 1302, while forecasting using the moving average method for a period of 3 months gives a result of 773 with an MSE value of 1135.728. Keywords: Double Exponential Smoothing, Forecasting, Moving Average